Emerging treatments in the management of schizophrenia – focus on sertindole - Maria Rosaria A Muscatello; Antonio Bruno; Gianluca Pandolfo; et al (Dove Medical Press, 2010)
Maria Rosaria A Muscatello, Antonio Bruno, Gianluca Pandolfo, Umberto Micò, Salvatore Settineri, Rocco ZoccaliSection of Psychiatry, Department of Neurosciences, Psychiatric and Anaesthesiological Sciences, University of Messina, ItalyAbstract: The antipsychotic treatment of schizophrenia is still marked by poor compliance, and drug discontinuation; the development of more effective and safer drugs still remains a challenge. Sertindole is a second-generation antipsychotic with high affinity for dopamine D2, serotonin 5-HT2A, 5-HT2C, and α1-adrenergic receptors, and low affinity for other receptors. Sertindole undergoes extensive hepatic metabolism by the cytochrome P450 isoenzymes CYP2D6 and CYP3A4 and has an elimination half-life of approximately three days. In controlled clinical trials sertindole was more effective than placebo in reducing positive and negative symptoms, whereas it was as effective as haloperidol and risperidone against the positive symptoms of schizophrenia. The effective dose-range of sertindole is 12–20 mg, administered orally once daily. The most common adverse events are headhache, insomnia, rhinitis/nasal congestion, male sexual dysfunction, and moderate weight gain, with few extrapyramidal symptoms and metabolic changes. Sertindole is associated with corrected QT interval prolongation, with subsequent risk of serious arrythmias. Due to cardiovascular safety concerns, sertindole is available as a second-line choice for patients intolerant to at least one other antipsychotic agent. Further clinical studies, mainly direct “head-to-head” comparisons with other second-generation antipsychotic agents, are needed to define the role of sertindole in the treatment of schizophrenia.Keywords: antipsychotics, pharmacology, pharmacokinetics, efficacy, safety